Analysis of SMEs Empowerment and Assistance in Laut Dendang Village - Riki Irawan Polem; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
One of the pillars of the national economy is supported by the presence of MSMEs. So that the efforts made by the government in the process of empowering MSMEs are always interesting topics to be reviewed. The purpose of this study was to investigate and analyze the empowerment of MSMEs in Laut Dendang Village and what assistance was obtained by MSME actors as a form of empowerment carried out by the government. This research uses descriptive qualitative method with triangulation analysis method through interview and observation. The results of the analysis show that the success of empowerment is conceptualized with five indicators. The three indicators, namely financial assistance, infrastructure to facilitate marketing results and training, have been realized quite well by the government. However, two other indicators deserve the government's attention on the aspects of facilities and infrastructure supporting business activities and strengthening community institutions. This is because the facilities and infrastructure that support business activities are one of the important factors that can support the performance and productivity of business actors. And institutional strengthening can open up opportunities to bridge MSME actors with various other government institutions and private parties to provide training and business development.